Rubidium and cesium ion adsorption material as well as preparation method and application thereof

By using polyphenol-modified heteropolyate ion sieve adsorbent in rubidium cesium ion adsorbent in rubidium cesium ion adsorbent material to conduct coupling reaction with polyvinyl alcohol and epoxy group-containing silane coupling agent, the problems of adsorbent powder encapsulation stability and adsorbent agglomeration are solved, and high saturation adsorption capacity and stability are achieved.

CN119793416AActive Publication Date: 2025-04-11CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202311315055.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-11
Publication Date
2025-04-11
Estimated Expiration
2043-10-11

AI Technical Summary

Technical Problem

The existing rubidium cesium ion adsorbent materials have problems in the adsorbent powder encapsulation stability and adsorbent agglomeration, resulting in unstable adsorption performance.

Method used

The heteropolyate ion sieve adsorbent modified with polyphenol is coupled with polyvinyl alcohol and epoxy group-containing silane coupling agent to form a skeleton with a network structure, which improves the stability and adsorption capacity of the adsorbent material.

Benefits of technology

The high saturation adsorption capacity of rubidium and cesium ions is achieved, while improving the stability of the adsorbent, ensuring that the adsorbent of heteropolyate ion sieve is not easy to fall off in an acidic environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004489364810000111
    Figure BDA0004489364810000111
  • Figure BDA0004489364810000181
    Figure BDA0004489364810000181
  • Figure BDA0004489364810000191
    Figure BDA0004489364810000191
Patent Text Reader

Abstract

The invention relates to the field of adsorption materials, and discloses a rubidium and cesium ion adsorption material and a preparation method and application thereof. The rubidium and cesium ion adsorption material comprises a skeleton and a polyphenol modified heteropolyacid salt ion sieve adsorbent dispersed in the skeleton, the framework is polyvinyl alcohol; the skeleton is connected with the polyphenol modified heteropolyacid salt ion sieve adsorbent through a silane coupling agent containing an epoxy group. The rubidium and cesium ion adsorption material can keep high rubidium and cesium saturation adsorption capacity, and has excellent stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of adsorption materials, and in particular to a rubidium-cesium ion adsorption material and a preparation method and application thereof. Background Art

[0002] my country's salt lake resources are rich and have mining value. Salt lakes are rich in lithium, sodium, potassium, rubidium, cesium and other resources. It is estimated that the reserves of cesium in Zabuye Salt Lake are 2,000 tons and rubidium is 5,000 tons. Rubidium and cesium are scarce resources in my country. Rubidium, cesium and their compound products have many applications in electronic devices, catalysts, special glass, biochemistry and medicine, as well as in the field of high-tech. Extracting rubidium and cesium from salt lakes is of great value.

[0003] The adsorption method for extracting rubidium and cesium ions from the solution has the advantages of high recovery rate and simple operation. Heteropolyacid salts such as ammonium phosphomolybdate and ammonium phosphotungstate have good ion exchange properties and large adsorption capacity, but their powder particles are small and have poor mechanical strength, and cannot be directly applied to conventional equipment such as fixed beds for adsorption-desorption. For this reason, some studies have used the sol-gel method to prepare spherical heteropolyacid composite exchangers, mixing the powder into gel balls, but the gel balls have poor strength and are easy to break after drying. Granulating the heteropolyacid powder to prepare stable granulated particles can effectively solve the above problems.

[0004] In summary, the development of acid- and alkali-resistant granulation technology for rubidium and cesium ion adsorption powder materials is of great significance to the future development of rubidium and cesium resources. Summary of the invention

[0005] The purpose of the present invention is to overcome the problems of poor stability of adsorbent powder wrapping and agglomeration of adsorbent powder in existing granulation products using polyvinyl alcohol as a skeleton, and to provide a rubidium-cesium ion adsorption material and its preparation method and application. The rubidium-cesium ion adsorption material can maintain a high saturated adsorption capacity of rubidium and cesium and has excellent stability.

[0006] In order to achieve the above-mentioned object, the first aspect of the present invention provides a rubidium-cesium ion adsorption material, wherein the rubidium-cesium ion adsorption material comprises a skeleton and a polyphenol-modified heteropolyacid salt ion sieve adsorbent dispersed in the skeleton;

[0007] The skeleton is polyvinyl alcohol; the skeleton and the polyphenol-modified heteropolyacid salt ion sieve adsorbent are connected via an epoxy-containing silane coupling agent.

[0008] A second aspect of the present invention provides a method for preparing a rubidium-cesium ion adsorption material, wherein the preparation method comprises the following steps:

[0009] (1) mixing and modifying a heteropoly acid salt ion sieve adsorbent and a polyphenol aqueous solution to obtain a polyphenol-modified heteropoly acid salt ion sieve adsorbent;

[0010] (2) mixing the polyphenol-modified heteropolyacid salt ion sieve adsorbent with a polyvinyl alcohol aqueous solution, adjusting the pH value, adding an epoxy-containing silane coupling agent to carry out a coupling reaction, and after the coupling reaction is carried out for a time T, adding a formaldehyde aqueous solution;

[0011] (3) Aging the product of step (2) to obtain a semi-solidified cross-linked product, and then extruding, granulating, and drying to obtain the rubidium-cesium ion adsorption material.

[0012] The third aspect of the present invention provides a rubidium-cesium ion adsorption material prepared by the above preparation method.

[0013] A fourth aspect of the present invention provides a use of the above-mentioned rubidium-cesium ion adsorption material in extracting rubidium and / or cesium ions.

[0014] Through the above technical scheme, the rubidium-cesium ion adsorption material provided by the present invention and its preparation method and application obtain the following beneficial effects.

[0015] The polyphenol-modified heteropolyacid salt ion sieve adsorbent in the rubidium-cesium ion adsorption material of the present invention can be connected to the polyvinyl alcohol forming a skeleton through a silane coupling agent containing an epoxy group. During long-term use, the heteropolyacid salt ion sieve adsorbent is not easy to fall off, and the polyphenol-modified heteropolyacid salt ion sieve adsorbent has excellent compatibility with the polyvinyl alcohol as a skeleton, so that the rubidium-cesium ion adsorption material has excellent stability while maintaining a high saturated adsorption capacity of rubidium and cesium.

[0016] Furthermore, under the synergistic effect of the epoxy-containing silane coupling agent and the polyphenol-modified heteropolyacid salt ion sieve adsorbent, the skeleton formed by the polyvinyl alcohol has a network structure, large porosity, and strong hydrophilicity, which is conducive to the rubidium-cesium ion adsorption material to adsorb rubidium and cesium ions in a water environment. In a long-term acidic environment, the heteropolyacid salt ion sieve adsorbent in the rubidium-cesium ion adsorption material is not easy to fall off and has excellent stability.

[0017] The preparation method of the rubidium-cesium ion adsorption material provided by the present invention adopts a polyphenol-modified heteropolyacid salt ion sieve adsorbent, polyvinyl alcohol and an epoxy-containing silane coupling agent to carry out a coupling reaction, and the obtained rubidium-cesium ion adsorption material has a high saturated adsorption capacity of rubidium and cesium and excellent stability. DETAILED DESCRIPTION

[0018] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0019] The first aspect of the present invention provides a rubidium-cesium ion adsorption material, wherein the rubidium-cesium ion adsorption material comprises a skeleton and a polyphenol-modified heteropolyacid salt ion sieve adsorbent dispersed in the skeleton;

[0020] The skeleton is polyvinyl alcohol; the skeleton and the polyphenol-modified heteropolyacid salt ion sieve adsorbent are connected via an epoxy-containing silane coupling agent.

[0021] In the present invention, the polyphenol-modified heteropolyacid salt ion sieve adsorbent in the rubidium-cesium ion adsorption material can be connected to the polyvinyl alcohol forming the skeleton through the epoxy-containing silane coupling agent. During long-term use, the heteropolyacid salt ion sieve adsorbent is not easy to fall off, and the polyphenol-modified heteropolyacid salt ion sieve adsorbent has excellent compatibility with the polyvinyl alcohol as the skeleton, so that the rubidium-cesium ion adsorption material has excellent stability while maintaining a high saturated adsorption capacity of rubidium and cesium.

[0022] Furthermore, under the synergistic effect of the epoxy-containing silane coupling agent and the polyphenol-modified heteropolyacid salt ion sieve adsorbent, the skeleton formed by the polyvinyl alcohol has a network structure, large porosity, and strong hydrophilicity, which is conducive to the rubidium-cesium ion adsorption material to adsorb rubidium and cesium ions in a water environment. In a long-term acidic environment, the heteropolyacid salt ion sieve adsorbent in the rubidium-cesium ion adsorption material is not easy to fall off and has excellent stability.

[0023] In the present invention, the polyphenol-modified heteropolyacid salt ion sieve adsorbent refers to a heteropolyacid salt ion sieve adsorbent having a polyphenol-modified layer formed by self-polymerization of polyphenols on the surface. The modified layer can improve the compatibility between the heteropolyacid salt ion sieve adsorbent and the high molecular polymer, so that the heteropolyacid salt ion sieve adsorbent has good dispersibility in the high molecular skeleton, and can make the adsorbent material have a high adsorption capacity.

[0024] According to the present invention, based on the total weight of the rubidium-cesium ion adsorption material, the content of the polyvinyl alcohol is 7wt%-17wt%, the content of the polyphenol-modified heteropolyacid salt ion sieve adsorbent is 25wt%-67wt%, and the content of the epoxy-containing silane coupling agent is 15wt%-65wt%.

[0025] In the present invention, based on the total weight of the rubidium-cesium ion adsorbent material, the sum of the content of the polyvinyl alcohol, the polyphenol-modified heteropolyacid ion sieve adsorbent and the epoxy-containing silane coupling agent is 100wt%. When the content of each component in the rubidium-cesium ion adsorbent material meets the above range, the mechanical strength of the adsorbent material can be ensured, making it difficult to break, and the adsorbent material can have a large adsorption capacity.

[0026] Furthermore, based on the total weight of the rubidium-cesium ion adsorption material, the content of the polyvinyl alcohol is 8wt%-13wt%, the content of the polyphenol-modified heteropolyacid salt ion sieve adsorbent is 35wt%-50wt%, and the content of the epoxy-containing silane coupling agent is 35wt%-55wt%.

[0027] According to the present invention, the thickness of the modified layer formed by polyphenol in the polyphenol-modified heteropolyacid salt ion sieve adsorbent is 2-15 nm.

[0028] In the present invention, when the thickness of the modified layer formed by polyphenols satisfies the above range, the polyphenol-modified heteropolyacid salt ion sieve adsorbent has excellent compatibility with the polymer, can be evenly dispersed in the polymer skeleton, and the loading amount of the heteropolyacid salt ion sieve adsorbent in the polymer skeleton is increased, so that the heteropolyacid salt ion sieve adsorbent in the adsorption material has a high specific surface area, thereby increasing the adsorption capacity of the material for adsorbing ions.

[0029] According to the present invention, the polyphenol is selected from at least one of tannic acid, tea polyphenol, dopamine, apple polyphenol, grape polyphenol, eriodictyol, naringenin, epicatechin, luteolin, naringenin, kaempferol, myricetin and genistein.

[0030] In the present invention, when the above polyphenols are selected, the compatibility between the heteropolyacid salt ion sieve adsorbent and the high molecular polymer can be improved, so that the polyphenol-modified heteropolyacid salt ion sieve adsorbent has better dispersibility in the high molecular skeleton, and the adsorption material has a high adsorption capacity.

[0031] Furthermore, the polyphenol is selected from at least one of tannic acid, tea polyphenols and dopamine.

[0032] According to the present invention, the heteropoly acid salt ion sieve adsorbent is selected from at least one of ammonium phosphomolybdate, ammonium phosphotungstate, arsenomolybdate, silicomolybdate, titanosilicate and hexagonal tungsten trioxide.

[0033] Furthermore, the heteropoly acid salt ion sieve adsorbent is ammonium phosphomolybdate.

[0034] According to the present invention, the epoxy-containing silane coupling agent is an epoxy-containing organosilane quaternary ammonium salt.

[0035] In the present invention, when an epoxy-containing organic silane quaternary ammonium salt is used, the lone pair of electrons on the tertiary amine N in the epoxy-containing organic silane quaternary ammonium salt can improve the reaction activity of the silane coupling agent; the prepared rubidium and cesium ion adsorption material has strong stability, and the quaternary ammonium group is beneficial to improving the hydrophilicity and adsorption capacity of the adsorption material.

[0036] Furthermore, the epoxy-containing silane coupling agent is selected from diethyl-2,3-epoxypropyl-[3-(methyldimethoxy)]silylpropyl ammonium chloride, diethyl-2,3-epoxypropyl-[3-(methyldimethoxy)]silylmethyl ammonium chloride, diethyl-2,3-epoxypropyl-[3-(methyldimethoxy)]silylethyl ammonium chloride, methyl-2,3-epoxypropyl-[3-(methyldimethoxy)]silylmethyl ammonium chloride, diethyl-2,3-epoxypropyl-[3-(methyldimethoxy)]silylethyl ammonium chloride, At least one of 2,3-epoxypropyl-[3-(methyldimethoxy)]silyl ammonium bromide, diethyl-2,3-epoxypropyl-[3-(methyldimethoxy)]silyl ammonium iodide, diethyl-2,3-epoxypropyl-[3-(methyldimethoxy)]silyl methyl ammonium bromide, diethyl-2,3-epoxypropyl-[3-(methyldimethoxy)]silyl ethyl ammonium bromide and methyl-2,3-epoxypropyl-[3-(methyldimethoxy)]silyl methyl ammonium bromide.

[0037] Furthermore, the epoxy-containing silane coupling agent is selected from at least one of diethyl-2,3-epoxypropyl-[3-(methyldimethoxy)]silaneethylammonium chloride, diethyl-2,3-epoxypropyl-[3-(methyldimethoxy)]silaneethylammonium chloride and diethyl-2,3-epoxypropyl-[3-(methyldimethoxy)]silaneethylammonium chloride; more preferably diethyl-2,3-epoxypropyl-[3-(methyldimethoxy)]silaneethylammonium chloride.

[0038] According to the present invention, the weight average molecular weight of the polyvinyl alcohol is 80,000-150,000 g / mol.

[0039] In the present invention, when the weight average molecular weight of the polyvinyl alcohol satisfies the above range, the mechanical strength of the adsorbent material is better.

[0040] Furthermore, the weight average molecular weight of the polyvinyl alcohol is 80,000-110,000 g / mol.

[0041] According to the present invention, the alcoholysis degree of the polyvinyl alcohol is 85-98%.

[0042] In the present invention, when the alcoholysis degree of polyvinyl alcohol satisfies the above range, the mechanical strength and hydrophilicity of the adsorbent material can be improved.

[0043] Furthermore, the alcoholysis degree of the polyvinyl alcohol is 85-90%.

[0044] According to the present invention, the average particle size of the rubidium-cesium ion adsorption material is 2-5 mm.

[0045] According to the present invention, the porosity of the rubidium-cesium ion adsorption material is 60-80%.

[0046] In the present invention, when the porosity of the rubidium-cesium ion adsorption material satisfies the above range, it indicates that the rubidium-cesium ion adsorption material has a small mass transfer resistance and a faster water mass transfer rate.

[0047] According to the present invention, the contact angle of the rubidium-cesium ion adsorption material is 30-52°.

[0048] In the present invention, when the contact angle of the rubidium-cesium ion adsorbent satisfies the above, it indicates that the rubidium-cesium ion adsorbent has excellent hydrophilicity.

[0049] A second aspect of the present invention provides a method for preparing a rubidium-cesium ion adsorption material, wherein the preparation method comprises the following steps:

[0050] (1) mixing and modifying a heteropoly acid salt ion sieve adsorbent and a polyphenol aqueous solution to obtain a polyphenol-modified heteropoly acid salt ion sieve adsorbent;

[0051] (2) mixing the polyphenol-modified heteropolyacid salt ion sieve adsorbent with a polyvinyl alcohol aqueous solution, adjusting the pH value, adding an epoxy-containing silane coupling agent to carry out a coupling reaction, and after the coupling reaction is carried out for a time T, adding a formaldehyde aqueous solution;

[0052] (3) Aging the product of step (2) to obtain a semi-solidified cross-linked product, and then extruding, granulating, and drying to obtain the rubidium-cesium ion adsorption material.

[0053] The preparation method of the rubidium-cesium ion adsorption material provided by the present invention adopts a polyphenol-modified heteropolyacid salt ion sieve adsorbent, polyvinyl alcohol and an epoxy-containing silane coupling agent to carry out a coupling reaction, and the obtained rubidium-cesium ion adsorption material has a high saturated adsorption capacity of rubidium and cesium and excellent stability.

[0054] According to the present invention, the heteropoly acid salt ion sieve adsorbent is selected from at least one of ammonium phosphomolybdate, ammonium phosphotungstate, arsenomolybdate, silicomolybdate, titanosilicate and hexagonal tungsten trioxide.

[0055] Furthermore, the heteropoly acid salt ion sieve adsorbent is ammonium phosphomolybdate.

[0056] According to the present invention, the polyphenol is selected from at least one of tannic acid, tea polyphenol, dopamine, apple polyphenol, grape polyphenol, eriodictyol, naringenin, epicatechin, luteolin, naringenin, kaempferol, myricetin and genistein.

[0057] In the present invention, when the above-mentioned polyphenols are selected, the compatibility between the heteropolyacid salt ion sieve adsorbent and the high molecular polymer can be improved, so that the polyphenol-modified heteropolyacid salt ion sieve adsorbent has better dispersibility in the high molecular skeleton, the adsorption material has a high adsorption capacity, and the modification conditions are milder.

[0058] Furthermore, the polyphenol is selected from at least one of tannic acid, tea polyphenols and dopamine.

[0059] According to the present invention, the concentration of the polyphenol aqueous solution is 0.1 mg / L-1 mg / L.

[0060] According to the present invention, the mass ratio of the heteropoly acid salt ion sieve adsorbent to the polyphenol is 1:0.1-1.

[0061] In the present invention, when the mass ratio of the ion sieve adsorbent to the polyphenol satisfies the above range, sufficient reaction can be ensured while the polyphenol can form a uniform coating layer on the surface of the heteropolyacid salt ion sieve adsorbent, and the dispersibility of the obtained polyphenol-modified heteropolyacid salt ion sieve adsorbent in the skeleton is significantly improved.

[0062] Furthermore, the mass ratio of the heteropoly acid salt ion sieve adsorbent to the polyphenol is 1:0.5-0.8.

[0063] According to the present invention, the mixed modification conditions include: modification time of 30min-4h, and modification temperature of 25-40°C.

[0064] In the present invention, when the mixed modification conditions meet the above range, it can ensure that the heteropolyacid salt ion sieve adsorbent and the polyphenol fully react, and the polyphenol can form a uniform coating layer on the surface of the heteropolyacid salt ion sieve adsorbent, and the dispersibility of the obtained hydroxyl-modified heteropolyacid salt ion sieve adsorbent in the skeleton is significantly improved.

[0065] According to the present invention, based on the total weight of the polyphenol-modified heteropolyacid salt ion sieve adsorbent, polyvinyl alcohol and the epoxy-containing silane coupling agent, the content of the polyvinyl alcohol is 7wt%-17wt%, the content of the polyphenol-modified heteropolyacid salt ion sieve adsorbent is 25wt%-67wt%, and the content of the epoxy-containing silane coupling agent is 15wt%-65wt%.

[0066] In the present invention, when the contents of the polyphenol-modified heteropolyacid salt ion sieve adsorbent, polyvinyl alcohol and epoxy-containing silane coupling agent meet the above ranges, the obtained adsorbent material has both good mechanical strength and large adsorption capacity.

[0067] Furthermore, based on the total weight of the polyphenol-modified heteropolyacid salt ion sieve adsorbent, polyvinyl alcohol and epoxy-containing silane coupling agent, the content of the polyvinyl alcohol is 8wt%-13wt%, the content of the polyphenol-modified heteropolyacid salt ion sieve adsorbent is 35wt%-50wt%, and the content of the epoxy-containing silane coupling agent is 35wt%-55wt%.

[0068] According to the present invention, the concentration of the polyvinyl alcohol aqueous solution is 10wt%-15wt%.

[0069] In the present invention, when the concentration of the polyvinyl alcohol aqueous solution meets the above range, the strength requirement of the rubidium and cesium ion adsorption material can be guaranteed.

[0070] According to the present invention, the epoxy-containing silane coupling agent is an epoxy-containing organosilane quaternary ammonium salt.

[0071] In the present invention, when an epoxy-containing organic silane quaternary ammonium salt is used, the lone pair of electrons on the tertiary amine N in the epoxy-containing organic silane quaternary ammonium salt can improve the reaction activity of the silane coupling agent; the prepared rubidium and cesium ion adsorption material has strong stability, and the quaternary ammonium group is beneficial to improving the hydrophilicity and adsorption capacity of the adsorption material.

[0072] Furthermore, the epoxy-containing silane coupling agent is selected from diethyl-2,3-epoxypropyl-[3-(methyldimethoxy)]silylpropyl ammonium chloride, diethyl-2,3-epoxypropyl-[3-(methyldimethoxy)]silylmethyl ammonium chloride, diethyl-2,3-epoxypropyl-[3-(methyldimethoxy)]silylethyl ammonium chloride, methyl-2,3-epoxypropyl-[3-(methyldimethoxy)]silylmethyl ammonium chloride, diethyl-2,3-epoxypropyl-[3-(methyldimethoxy)]silylethyl ammonium chloride, At least one of 2,3-epoxypropyl-[3-(methyldimethoxy)]silyl ammonium bromide, diethyl-2,3-epoxypropyl-[3-(methyldimethoxy)]silyl ammonium iodide, diethyl-2,3-epoxypropyl-[3-(methyldimethoxy)]silyl methyl ammonium bromide, diethyl-2,3-epoxypropyl-[3-(methyldimethoxy)]silyl ethyl ammonium bromide and methyl-2,3-epoxypropyl-[3-(methyldimethoxy)]silyl methyl ammonium bromide.

[0073] Furthermore, the epoxy-containing silane coupling agent is selected from at least one of diethyl-2,3-epoxypropyl-[3-(methyldimethoxy)]silaneethylammonium chloride, diethyl-2,3-epoxypropyl-[3-(methyldimethoxy)]silaneethylammonium chloride and diethyl-2,3-epoxypropyl-[3-(methyldimethoxy)]silaneethylammonium chloride; more preferably diethyl-2,3-epoxypropyl-[3-(methyldimethoxy)]silaneethylammonium chloride.

[0074] According to the present invention, the weight average molecular weight of the polyvinyl alcohol is 80,000-150,000 g / mol.

[0075] In the present invention, when the weight average molecular weight of the polyvinyl alcohol satisfies the above range, the mechanical strength of the adsorbent material is better.

[0076] Furthermore, the weight average molecular weight of the polyvinyl alcohol is 80,000-110,000 g / mol.

[0077] According to the present invention, the alcoholysis degree of the polyvinyl alcohol is 85-98%.

[0078] In the present invention, when the alcoholysis degree of polyvinyl alcohol satisfies the above range, the mechanical strength and hydrophilicity of the adsorbent material can be improved.

[0079] Furthermore, the alcoholysis degree of the polyvinyl alcohol is 85-90%.

[0080] According to the present invention, in step (2), the pH value is 1-3.

[0081] According to the present invention, the coupling reaction conditions include: the coupling reaction temperature is 50-70° C., and the coupling reaction time is 40 min-4 h.

[0082] According to the present invention, the coupling reaction is carried out for a time T≥30min.

[0083] In the present invention, when the time T is greater than or equal to 30 min, the obtained rubidium-cesium ion adsorption material has a high degree of cross-linking.

[0084] According to the present invention, the concentration of the formaldehyde aqueous solution is 1wt%-4wt%.

[0085] In the present invention, when the concentration of the formaldehyde aqueous solution meets the above range, the obtained rubidium and cesium ion adsorption material can ensure the cross-linking effect while not being too dense.

[0086] According to the present invention, the mass ratio of the polyvinyl alcohol to the formaldehyde is 5-20:1.

[0087] According to the present invention, in step (3), the aging conditions include: aging temperature of 30-40° C., and aging time of 5-100 min.

[0088] In the present invention, step (1) comprises: mixing and modifying the heteropoly acid salt ion sieve adsorbent with the polyphenol aqueous solution, centrifuging and drying to obtain the polyphenol-modified heteropoly acid salt ion sieve adsorbent. Preferably, the water content of the polyphenol-modified heteropoly acid salt ion sieve adsorbent is less than or equal to 0.5wt%.

[0089] In the present invention, the preparation method further comprises: eluting the rubidium-cesium ion adsorption material with an acidic solution. Preferably, the acidic solution is selected from hydrochloric acid and / or sulfuric acid. Preferably, the concentration of the acidic solution is 0.01-1 mol / L. Preferably, the elution time is 0.5-24h.

[0090] The third aspect of the present invention provides a rubidium-cesium ion adsorption material prepared by the above preparation method.

[0091] A fourth aspect of the present invention provides a use of the above-mentioned rubidium-cesium ion adsorption material in extracting rubidium and / or cesium ions.

[0092] The present invention will be described in detail below through examples.

[0093] In the following examples and comparative examples, the properties involved are obtained by the following methods:

[0094] Dynamic adsorption and desorption cycle method of rubidium-cesium ion adsorbent material: The obtained rubidium-cesium ion adsorbent material (4 g) was placed in a glass column for acid washing (using 400 mL of 0.5 M hydrochloric acid at 30°C, the hydrochloric acid flow rate was 2 mL / min), and then 400 mL of rubidium carbonate solution (RbCO3) was pumped into the column at a flow rate of 2 mL / min using a peristaltic pump. + concentration of 200ppm, pH = 10) or 400mL cesium carbonate solution (cesium carbonate Cs 2+ The concentration is 50ppm, pH=7.6), and the dynamic adsorption-desorption cycle is carried out for 24 hours. Then, 0.5M hydrochloric acid (200mL) is pumped in at a flow rate of 2mL / min with a peristaltic pump, and the rubidium ions or cesium ions in the particles are desorbed for 24 hours. Then, the particles are washed with deionized water until neutral, which is one cycle.

[0095] Saturated adsorption capacity of rubidium and cesium ions: Monitor the change of adsorption capacity over time during a dynamic adsorption-desorption cycle and calculate the saturated adsorption capacity Q. The calculation formula is as follows:

[0096]

[0097] Wherein, Q is the saturated adsorption capacity, in mg / g, which reflects the adsorption amount of the rubidium-cesium ion adsorption material when the adsorption reaches equilibrium; C0 and C are the initial and saturated ion concentrations in the solution, in mg / L, respectively; V is the volume of the rubidium carbonate solution or the cesium carbonate solution, in L; m is the mass of the rubidium-cesium ion adsorption material, in g.

[0098] Ion concentration of rubidium and cesium ions: Ion concentration was measured using ion chromatography (ICS-1100, DIONEX, America).

[0099] Contact angle of rubidium-cesium ion adsorption material: The contact angle was tested using a DSA100 surface contact angle measuring instrument produced by KRUSS, Germany.

[0100] Porosity of rubidium-cesium ion adsorption material: measured by porosity tester.

[0101] Mass loss ratio of rubidium-cesium ion adsorption material: the weighing method is adopted, that is, the mass of the adsorption material before use (i.e., the initial mass) and the mass of the adsorption material after 30 adsorption-desorption cycles are weighed respectively, and the ratio of the lost mass to the initial mass is the mass loss ratio.

[0102] In the rubidium and cesium ion adsorption material, the contents of polyvinyl alcohol, polyphenol-modified heteropolyacid salt ion sieve adsorbent and epoxy-containing silane coupling agent are calculated by the feed ratio of the raw materials corresponding to each structural unit.

[0103] Average particle size of the rubidium-cesium ion adsorption material and thickness of the modified layer: The thickness of the modified layer of the modified powder was characterized by scanning electron microscopy (SEM, S-4800).

[0104] The weight average molecular weight of polyvinyl alcohol is measured by gel permeation chromatography (GPC).

[0105] Diethyl-2,3-epoxypropyl-[3-(methyldimethoxy)]silaneethylammonium chloride was purchased from Inokai

[0106] Diethyl-2,3-epoxypropyl-[3-(methyldimethoxy)]silylmethylammonium chloride was purchased from Inotech.

[0107] Diethyl-2,3-epoxypropyl-[3-(methyldimethoxy)]silylpropylammonium chloride was purchased from Inotech.

[0108] Polyvinyl alcohol A: The alcoholysis degree is 88%, and the weight average molecular weight is 89,000 g / mol.

[0109] Polyvinyl alcohol B: alcoholysis degree is 95%, and weight average molecular weight is 12,000 g / mol.

[0110] In the following examples and comparative examples, the room temperature is 25°C.

[0111] Other raw materials used in the preparation examples, embodiments and comparative examples are all commercially available.

[0112] Preparation Example 1

[0113] Ammonium phosphomolybdate powder was mixed with an aqueous solution of tannic acid (wherein the concentration of tannic acid was 0.1 mg / L) so that the mass ratio of the heteropolyacid salt ion sieve adsorbent to the polyphenol was 1:0.1, and the modification was stirred at room temperature for 2 h.

[0114] The mixed solution was centrifuged and the solid phase material was dried to obtain a polyphenol-modified heteropolyacid salt ion sieve adsorbent A, the water content of which was 0.3 wt%.

[0115] Preparation Example 2

[0116] Ammonium phosphomolybdate powder was mixed with an aqueous solution of dopamine (wherein the concentration of dopamine was 0.5 mg / L) so that the mass ratio of the heteropolyacid salt ion sieve adsorbent to the polyphenol was 1:0.5, and the modified mixture was stirred at room temperature for 2 h.

[0117] The mixed solution was centrifuged and the solid phase material was dried to obtain a polyphenol-modified heteropolyacid salt ion sieve adsorbent B, whose water content was 0.3 wt %.

[0118] Preparation Example 3

[0119] Ammonium phosphomolybdate powder was mixed with an aqueous solution of catechol (wherein the concentration of catechol was 1 mg / L) so that the mass ratio of the heteropolyacid salt ion sieve adsorbent to the polyphenol was 1:1, and the modification was stirred at room temperature for 2 h.

[0120] The mixed solution was centrifuged and the solid phase material was dried to obtain a polyphenol-modified heteropolyacid salt ion sieve adsorbent C, which had a water content of 0.3 wt%.

[0121] Preparation Example 4

[0122] Ammonium phosphomolybdate powder was mixed with an aqueous solution of catechin (wherein the concentration of catechin was 0.1 mg / L) so that the mass ratio of the heteropolyacid salt ion sieve adsorbent to the polyphenol was 1:0.1, and the modified mixture was stirred at room temperature for 2 h.

[0123] The mixed solution was centrifuged and the solid phase material was dried to obtain a polyphenol-modified heteropolyacid salt ion sieve adsorbent D, the water content of which was 0.3 wt%.

[0124] Preparation Example 5

[0125] Ammonium phosphomolybdate powder was mixed with an aqueous solution of polyvinyl alcohol (Mw=1000) (wherein the concentration of polyvinyl alcohol was 0.1 mg / L) so that the mass ratio of the heteropolyacid salt ion sieve adsorbent to the polyvinyl alcohol was 1:0.1, and the modified mixture was stirred at room temperature for 2 h.

[0126] The mixed solution was centrifuged and the solid phase material was dried to obtain a polyvinyl alcohol-modified heteropolyacid salt ion sieve adsorbent E, whose water content was 0.3 wt %.

[0127] Example 1

[0128] (1) The polyphenol-modified heteropoly acid salt ion sieve adsorbent A and a 15 wt % aqueous solution of polyvinyl alcohol A are mixed and stirred uniformly, and after adjusting the pH to 1 with 0.1 M HCl, the mixture is stirred uniformly at 70° C., and diethyl-2,3-epoxypropyl-[3-(methyldimethoxy)]silylethylammonium chloride is added. Based on the total weight of the polyphenol-modified heteropoly acid salt ion sieve adsorbent, polyvinyl alcohol and epoxy-containing silane coupling agent, the content of the polyvinyl alcohol is 9.1 wt %, the content of the polyphenol-modified heteropoly acid salt ion sieve adsorbent is 36.4 wt %, and the content of the epoxy-containing silane coupling agent is 54.5 wt %. The mixture is coupled at 70° C. for 2 h, and 1 mL of a 1 wt % formaldehyde aqueous solution is added when the coupling reaction is carried out for 30 min (the mass ratio of polyvinyl alcohol to the formaldehyde is 15:1).

[0129] (2) The product of the first step is placed at 40° C. for 30 minutes for aging to obtain a semi-solidified cross-linked product, which is then extruded, granulated, and dried to obtain a rubidium-cesium ion adsorption material with an average particle size of 2.5 mm.

[0130] Example 2

[0131] (1) The polyphenol-modified heteropoly acid salt ion sieve adsorbent B and a 15 wt % aqueous solution of polyvinyl alcohol A are mixed and stirred uniformly, and after adjusting the pH to 1 with 0.5 M HCl, the mixture is stirred uniformly at 70° C., and diethyl-2,3-epoxypropyl-[3-(methyldimethoxy)]silylethylammonium chloride is added. Based on the total weight of the polyphenol-modified heteropoly acid salt ion sieve adsorbent, polyvinyl alcohol and epoxy-containing silane coupling agent, the content of the polyvinyl alcohol is 7.1 wt %, the content of the polyphenol-modified heteropoly acid salt ion sieve adsorbent is 28.6 wt %, and the content of the epoxy-containing silane coupling agent is 64.3 wt %. The mixture is coupled at 70° C. for 2 h, and 1 mL of 1 % formaldehyde aqueous solution is added when the coupling reaction is carried out for 30 min (the mass ratio of polyvinyl alcohol to the formaldehyde is 15:1).

[0132] (2) The product of the first step is placed at 40° C. for 30 minutes for aging to obtain a semi-solidified cross-linked product, which is then extruded, granulated, and dried to obtain a rubidium-cesium ion adsorption material with an average particle size of 2.5 mm.

[0133] Example 3

[0134] (1) The polyphenol-modified heteropoly acid salt ion sieve adsorbent C and a 15 wt % aqueous solution of polyvinyl alcohol A are mixed and stirred uniformly, and after adjusting the pH to 1 with 0.5 M HCl, the mixture is stirred uniformly at 70° C., and diethyl-2,3-epoxypropyl-[3-(methyldimethoxy)]silylethylammonium chloride is added. Based on the total weight of the polyphenol-modified heteropoly acid salt ion sieve adsorbent, polyvinyl alcohol and epoxy-containing silane coupling agent, the content of the polyvinyl alcohol is 16.7 wt %, the content of the polyphenol-modified heteropoly acid salt ion sieve adsorbent is 66.6 wt %, and the content of the epoxy-containing silane coupling agent is 16.7 wt %. The mixture is coupled at 70° C. for 2 h, and 1 mL of 1 % formaldehyde aqueous solution is added after the coupling reaction is carried out for 30 min (the mass ratio of polyvinyl alcohol to the formaldehyde is 15:1).

[0135] (2) The product of the first step is placed at 40° C. for 30 minutes for aging to obtain a semi-solidified cross-linked product, which is then extruded, granulated, and dried to obtain a rubidium-cesium ion adsorption material with an average particle size of 2.5 mm.

[0136] Example 4

[0137] The rubidium and cesium ion adsorbent material was prepared according to the method of Example 1, except that the polyphenol-modified heteropolyacid salt ion sieve adsorbent A was replaced by the polyphenol-modified heteropolyacid salt ion sieve adsorbent D.

[0138] Example 5

[0139] The rubidium and cesium ion adsorption material was prepared according to the method of Example 1, except that the silane coupling agent diethyl-2,3-epoxypropyl-[3-(methyldimethoxy)]silylethylammonium chloride in step 1 was replaced by diethyl-2,3-epoxypropyl-[3-(methyldimethoxy)]silylmethylammonium chloride.

[0140] Example 6

[0141] The rubidium and cesium ion adsorption material was prepared according to the method of Example 1, except that the silane coupling agent diethyl-2,3-epoxypropyl-[3-(methyldimethoxy)]silylethylammonium chloride in step 1 was replaced by diethyl-2,3-epoxypropyl-[3-(methyldimethoxy)]silylpropylammonium chloride.

[0142] Example 7

[0143] (1) The polyphenol-modified heteropoly acid salt ion sieve adsorbent A and a 15 wt % aqueous solution of polyvinyl alcohol A are mixed and stirred uniformly, and after adjusting the pH to 1 with 0.1 M HCl, the mixture is stirred uniformly at 70° C., and diethyl-2,3-epoxypropyl-[3-(methyldimethoxy)]silylethylammonium chloride is added. Based on the total weight of the polyphenol-modified heteropoly acid salt ion sieve adsorbent, polyvinyl alcohol and epoxy-containing silane coupling agent, the content of the polyvinyl alcohol is 12.5 wt %, the content of the polyphenol-modified heteropoly acid salt ion sieve adsorbent is 50 wt %, and the content of the epoxy-containing silane coupling agent is 37.5 wt %. The mixture is coupled at 70° C. for 2 h, and 1 mL of 1 % formaldehyde aqueous solution is added when the coupling reaction is carried out for 30 min (the mass ratio of polyvinyl alcohol to the formaldehyde is 15:1).

[0144] (2) The product of the first step is placed at 40° C. for 30 minutes for aging to obtain a semi-solidified cross-linked product, which is then extruded, granulated, and dried to obtain a rubidium-cesium ion adsorption material with an average particle size of 2.5 mm.

[0145] Example 8

[0146] (1) The polyphenol-modified heteropoly acid salt ion sieve adsorbent A and a 9wt% aqueous solution of polyvinyl alcohol B were mixed and stirred uniformly, and after adjusting the pH to 1 with 0.1M HCl, the mixture was stirred uniformly at 70°C, and diethyl-2,3-epoxypropyl-[3-(methyldimethoxy)]silylethylammonium chloride was added. Based on the total weight of the polyphenol-modified heteropoly acid salt ion sieve adsorbent, polyvinyl alcohol and epoxy-containing silane coupling agent, the content of the polyvinyl alcohol was 9.1wt%, the content of the polyphenol-modified heteropoly acid salt ion sieve adsorbent was 36.4wt%, and the content of the epoxy-containing silane coupling agent was 54.5wt%. The mixture was coupled at 70°C for 2h, and 1mL of 1% formaldehyde aqueous solution was added when the coupling reaction was carried out for 30min (the mass ratio of polyvinyl alcohol to the formaldehyde was 15:1).

[0147] (2) The product of the first step is placed at 40° C. for 30 minutes for aging to obtain a semi-solidified cross-linked product, which is then extruded, granulated, and dried to obtain a rubidium-cesium ion adsorption material with an average particle size of 2.5 mm.

[0148] Example 9

[0149] (1) The polyphenol-modified heteropoly acid salt ion sieve adsorbent A and a 15 wt % aqueous solution of polyvinyl alcohol A are mixed and stirred uniformly, and after adjusting the pH to 1 with 0.1 M HCl, the mixture is stirred uniformly at 70° C., and diethyl-2,3-epoxypropyl-[3-(methyldimethoxy)]silylethylammonium chloride is added. Based on the total weight of the polyphenol-modified heteropoly acid salt ion sieve adsorbent, polyvinyl alcohol and epoxy-containing silane coupling agent, the content of the polyvinyl alcohol is 14.1 wt %, the content of the polyphenol-modified heteropoly acid salt ion sieve adsorbent is 84.5 wt %, and the content of the epoxy-containing silane coupling agent is 1.4 wt %. The mixture is coupled at 70° C. for 2 h, and 1 mL of a 1 wt % formaldehyde aqueous solution is added when the coupling reaction is carried out for 30 min (the mass ratio of polyvinyl alcohol to the formaldehyde is 15:1).

[0150] (2) The product of the first step is placed at 40° C. for 30 minutes for aging to obtain a semi-solidified cross-linked product, which is then extruded, granulated, and dried to obtain a rubidium-cesium ion adsorption material with an average particle size of 2.5 mm.

[0151] Example 10

[0152] The rubidium and cesium ion adsorption material was prepared according to the method of Example 1, except that diethyl-2,3-epoxypropyl-[3-(methyldimethoxy)]silylethylammonium chloride was replaced by γ-(2,3-epoxypropyloxy)propyltrimethoxysilane.

[0153] Comparative Example 1

[0154] The rubidium-cesium ion adsorption material was prepared according to the method of Example 1, except that the polyphenol-modified heteropolyacid salt ion sieve adsorbent A was replaced with ammonium phosphomolybdate powder, that is, the ammonium phosphomolybdate powder was not modified. Based on the total weight of the heteropolyacid salt ion sieve adsorbent, polyvinyl alcohol and epoxy-containing silane coupling agent, the content of the polyvinyl alcohol was 9.1wt%, the content of the heteropolyacid salt ion sieve adsorbent was 36.4wt%, and the content of the epoxy-containing silane coupling agent was 54.5wt%.

[0155] Comparative Example 2

[0156] The rubidium and cesium ion adsorbent material was prepared according to the method of Example 1, except that the epoxy-containing silane coupling agent was not added. Based on the total weight of the heteropoly acid salt ion sieve adsorbent and the polyvinyl alcohol, the content of the polyvinyl alcohol was 20 wt %, and the content of the polyphenol-modified heteropoly acid salt ion sieve adsorbent was 80 wt %.

[0157] Comparative Example 3

[0158] The rubidium-cesium ion adsorbent material was prepared according to the method of Example 1, except that the formaldehyde aqueous solution was replaced by a borax aqueous solution (2 wt%). The content of the heteropoly acid salt ion sieve adsorbent, the polyvinyl alcohol, the polyphenol-modified heteropoly acid salt ion sieve adsorbent, was 9.1 wt%, the content of the polyphenol-modified heteropoly acid salt ion sieve adsorbent was 36.4 wt%, and the content of the borax was 54.9 wt%.

[0159] Comparative Example 4

[0160] The rubidium and cesium ion adsorbent material was prepared according to the method of Example 1, except that the polyphenol-modified heteropolyacid salt ion sieve adsorbent A was replaced by the polyvinyl alcohol-modified heteropolyacid salt ion sieve adsorbent E.

[0161] In the present invention, the content of polyvinyl alcohol, the content of polyphenol-modified heteropolyacid salt ion sieve adsorbent, and the content of epoxy-containing silane coupling agent in the heteropolyacid salt ion sieve adsorbent of the embodiments and comparative examples are shown in Table 1. The modified layer thickness, porosity, contact angle, rubidium ion saturation adsorption capacity Q of the heteropolyacid salt ion sieve adsorbent of the embodiments and comparative examples Rb , cesium ion saturation adsorption capacity Q Cs The mass loss ratios are shown in Table 2.

[0162] Table 1

[0163]

[0164] Table 2

[0165]

[0166] It can be seen from the results that compared with the comparative example, the comprehensive performance of the rubidium-cesium ion adsorption material of the present invention is better. The saturated adsorption capacity of the rubidium-cesium ion adsorption material of the present invention for rubidium is greater than or equal to 11 mg / g, and the saturated adsorption capacity for cesium is greater than or equal to 6 mg / g; and the dynamic adsorption and desorption cycle is repeated 30 times, and the mass loss ratio is less than or equal to 2.5wt%; it shows that the rubidium-cesium ion adsorption material prepared by the scheme of the present invention has a high saturated adsorption capacity of rubidium and cesium. At the same time, the structure of the adsorption material is stable, and the heteropolyacid salt ion sieve adsorbent is not easy to fall off after long-term use, and has good acid resistance.

[0167] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A rubidium-cesium ion adsorption material, characterized in that: The rubidium-cesium ion adsorption material comprises a skeleton and a polyphenol-modified heteropolyacid salt ion sieve adsorbent dispersed in the skeleton; The skeleton is polyvinyl alcohol; the skeleton and the polyphenol-modified heteropolyacid salt ion sieve adsorbent are connected via an epoxy-containing silane coupling agent.

2. The rubidium-cesium ion adsorbent according to claim 1, wherein: Based on the total weight of the rubidium-cesium ion adsorbent material, the content of the polyvinyl alcohol is 7wt%-17wt%, the content of the polyphenol-modified heteropolyacid salt ion sieve adsorbent is 25wt%-67wt%, and the content of the epoxy-containing silane coupling agent is 15wt%-65wt%; Preferably, based on the total weight of the rubidium-cesium ion adsorption material, the content of the polyvinyl alcohol is 8wt%-13wt%, the content of the polyphenol-modified heteropolyacid salt ion sieve adsorbent is 35wt%-50wt%, and the content of the epoxy-containing silane coupling agent is 35wt%-55wt%.

3. The rubidium-cesium ion adsorbent according to claim 1 or 2, wherein: The thickness of the modified layer formed by polyphenol in the polyphenol-modified heteropolyacid salt ion sieve adsorbent is 2-15 nm; Preferably, the polyphenol is selected from at least one of tannic acid, tea polyphenol, dopamine, apple polyphenol, grape polyphenol, eriodictyol, naringenin, epicatechin, luteolin, naringenin, kaempferol, myricetin and genistein; Preferably, the heteropoly acid salt ion sieve adsorbent is selected from at least one of ammonium phosphomolybdate, ammonium phosphotungstate, arsenomolybdate, silicomolybdate, titanosilicate and hexagonal tungsten trioxide.

4. The rubidium-cesium ion adsorption material according to any one of claims 1 to 3, wherein: The epoxy-containing silane coupling agent is an epoxy-containing organic silane quaternary ammonium salt; Preferably, the epoxy-containing silane coupling agent is selected from diethyl-2,3-epoxypropyl-[3-(methyldimethoxy)]silylpropyl ammonium chloride, diethyl-2,3-epoxypropyl-[3-(methyldimethoxy)]silylmethyl ammonium chloride, diethyl-2,3-epoxypropyl-[3-(methyldimethoxy)]silylethyl ammonium chloride, methyl-2,3-epoxypropyl-[3-(methyldimethoxy)]silylmethyl ammonium chloride, diethyl-2,3-epoxypropyl-[3-(methyldimethoxy)]silylethyl ammonium chloride, At least one of propyl-[3-(methyldimethoxy)]silylpropylammonium bromide, diethyl-2,3-epoxypropyl-[3-(methyldimethoxy)]silylpropylammonium iodide, diethyl-2,3-epoxypropyl-[3-(methyldimethoxy)]silylmethylammonium bromide, diethyl-2,3-epoxypropyl-[3-(methyldimethoxy)]silylethylammonium bromide and methyl-2,3-epoxypropyl-[3-(methyldimethoxy)]silylmethylammonium bromide; Preferably, the weight average molecular weight of the polyvinyl alcohol is 80,000-150,000 g / mol; Preferably, the alcoholysis degree of the polyvinyl alcohol is 85-98%.

5. The rubidium-cesium ion adsorption material according to any one of claims 1 to 4, wherein: The average particle size of the rubidium-cesium ion adsorption material is 2-5 mm; Preferably, the porosity of the rubidium-cesium ion adsorption material is 60-80%; Preferably, the contact angle of the rubidium-cesium ion adsorption material is 30-52°.

6. A method for preparing a rubidium-cesium ion adsorption material, characterized in that: The preparation method comprises the following steps: (1) mixing and modifying a heteropoly acid salt ion sieve adsorbent and a polyphenol aqueous solution to obtain a polyphenol-modified heteropoly acid salt ion sieve adsorbent; (2) mixing the polyphenol-modified heteropolyacid salt ion sieve adsorbent with a polyvinyl alcohol aqueous solution, adjusting the pH value, adding an epoxy-containing silane coupling agent to carry out a coupling reaction, and after the coupling reaction is carried out for a time T, adding a formaldehyde aqueous solution; (3) Aging the product of step (2) to obtain a semi-solidified cross-linked product, and then extruding, granulating, and drying to obtain the rubidium-cesium ion adsorption material.

7. The preparation method according to claim 6, wherein: The heteropoly acid salt ion sieve adsorbent is selected from at least one of ammonium phosphomolybdate, ammonium phosphotungstate, arsenomolybdate, silicomolybdate, titanosilicate and hexagonal tungsten trioxide; Preferably, the polyphenol is selected from at least one of tannic acid, tea polyphenol, dopamine, apple polyphenol, grape polyphenol, eriodictyol, naringenin, epicatechin, luteolin, naringenin, kaempferol, myricetin and genistein; Preferably, the concentration of the polyphenol aqueous solution is 0.1 mg / L-1 mg / L; Preferably, the mass ratio of the heteropoly acid salt ion sieve adsorbent to the polyphenol is 1:0.1-1; Preferably, the mixed modification conditions include: modification time of 30 min-4 h, and modification temperature of 25-40°C.

8. The preparation method according to claim 6 or 7, wherein: Based on the total weight of the polyphenol-modified heteropoly acid salt ion sieve adsorbent, polyvinyl alcohol and the epoxy-containing silane coupling agent, the content of the polyvinyl alcohol is 7wt%-17wt%, the content of the polyphenol-modified heteropoly acid salt ion sieve adsorbent is 25wt%-67wt%, and the content of the epoxy-containing silane coupling agent is 15wt%-65wt%; Preferably, based on the total weight of the polyphenol-modified heteropoly acid salt ion sieve adsorbent, polyvinyl alcohol and the epoxy-containing silane coupling agent, the content of the polyvinyl alcohol is 8wt%-13wt%, the content of the polyphenol-modified heteropoly acid salt ion sieve adsorbent is 35wt%-50wt%, and the content of the epoxy-containing silane coupling agent is 35wt%-55wt%; Preferably, the concentration of the polyvinyl alcohol aqueous solution is 10wt%-15wt%; Preferably, the epoxy-containing silane coupling agent is an epoxy-containing organosilane quaternary ammonium salt; Preferably, the epoxy-containing silane coupling agent is selected from diethyl-2,3-epoxypropyl-[3-(methyldimethoxy)]silylpropyl ammonium chloride, diethyl-2,3-epoxypropyl-[3-(methyldimethoxy)]silylmethyl ammonium chloride, diethyl-2,3-epoxypropyl-[3-(methyldimethoxy)]silylethyl ammonium chloride, methyl-2,3-epoxypropyl-[3-(methyldimethoxy)]silylmethyl ammonium chloride, diethyl-2,3-epoxypropyl-[3-(methyldimethoxy)]silylethyl ammonium chloride, At least one of propyl-[3-(methyldimethoxy)]silylpropylammonium bromide, diethyl-2,3-epoxypropyl-[3-(methyldimethoxy)]silylpropylammonium iodide, diethyl-2,3-epoxypropyl-[3-(methyldimethoxy)]silylmethylammonium bromide, diethyl-2,3-epoxypropyl-[3-(methyldimethoxy)]silylethylammonium bromide and methyl-2,3-epoxypropyl-[3-(methyldimethoxy)]silylmethylammonium bromide; Preferably, the weight average molecular weight of the polyvinyl alcohol is 80,000-150,000 g / mol; Preferably, the alcoholysis degree of the polyvinyl alcohol is 85-98%.

9. The preparation method according to any one of claims 6 to 8, wherein: In step (2), the pH value is 1-3; Preferably, the coupling reaction conditions include: coupling reaction temperature of 50-70°C, coupling reaction time of 40min-4h; Preferably, the coupling reaction is carried out for a time T≥30min; Preferably, the concentration of the formaldehyde aqueous solution is 1wt%-4wt%; Preferably, the mass ratio of the polyvinyl alcohol to the formaldehyde is 5-20:1; Preferably, in step (3), the aging conditions include: aging temperature of 30-40° C., and aging time of 5-100 min.

10. The rubidium-cesium ion adsorption material prepared by the preparation method according to any one of claims 6 to 9.

11. Use of the rubidium-cesium ion adsorption material according to any one of claims 1 to 5 and 10 in extracting rubidium and / or cesium ions.

Citation Information

Patent Citations

  • Preparation method of quaternary ammonium type lignin / poval composite material for adsorbing TNT (2,4,6-trinitrotoluene)

    CN102504289A

  • Polyving alcohol composite hydrogel and preparation method thereof

    CN103665685A

  • Composite hydrogel for adsorption of heavy metal ions and preparation method thereof

    CN104226281A

  • Preparation method of rubidium ion adsorption microsphere

    CN109908877A

  • Preparation method of covalent organic framework hydrogel and application of covalent organic framework hydrogel to uranium adsorption

    CN113185717A